Analisis Minat Belajar Siswa pada Mata Pelajaran Biologi Kelas X SMA Negeri 1 Aek Natas - Sembiring, Putri Wulandari; Nazliah, Rahmi; Irmayanti, Irmayanti (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The aim of this research is to identify students' learning interests in class X Biology at SMA Negeri 1 Aek Natas, Aek Natas District, North Labuhanbatu Regency. This research was conducted using a descriptive qualitative approach. The research strategy applied was to analyze students' interest in learning at SMA Negeri 1 Aek Natas. The method used in this research was a questionnaire given to 29 class X students of SMA Negeri 1 Aek Natas. The questionnaire is filled out via the Google Form Platform. There are four indicators that are measured in evaluating students' interest in learning Biology in class The results of the research show that students' interest in learning in class X SMA Negeri 1 Aek Natas is 53.6%. In detail, the percentage of student interest for the knowledge indicator was 62.05%, the activeness indicator was 55.7%, the attention indicator was 48.3%, and the interest indicator was 48.3%. This percentage was obtained by filling out a questionnaire distributed to students. Based on these results, it can be concluded that students' interest in learning Biology in class X SMA Negeri 1 Aek Natas can be categorized as moderate interest.